2017
DOI: 10.1038/srep44681
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mangiferin as a potential Glucokinase activator by structure-based virtual ligand screening

Abstract: The natural product mangiferin (compound 7) has been identified as a potential glucokinase activator by structure-based virtual ligand screening. It was proved by enzyme activation experiment and cell-based assays in vitro, with potency in micromolar range. Meanwhile, this compound showed good antihyperglycemic activity in db/db mice without obvious side effects such as excessive hypoglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 33 publications
(41 reference statements)
0
13
0
2
Order By: Relevance
“…A more recent work by Min et al [120], using structure-based virtual ligand screening identified mangiferin as a potential glucokinase activator. In the same study, using an in vitro cell-based assay, mangiferin was shown to effectively improve postprandial blood glucose levels by promoting a remarkable enhancement of glucose consumption in HepG2 and C2C12 cells.…”
Section: South African Herbal Tisanesmentioning
confidence: 99%
“…A more recent work by Min et al [120], using structure-based virtual ligand screening identified mangiferin as a potential glucokinase activator. In the same study, using an in vitro cell-based assay, mangiferin was shown to effectively improve postprandial blood glucose levels by promoting a remarkable enhancement of glucose consumption in HepG2 and C2C12 cells.…”
Section: South African Herbal Tisanesmentioning
confidence: 99%
“…For example, in the discovery of GK activator, the half maximal effective concentration (EC 50 ) of synthesized activator TMG-123 was <1 µM, 129 while to our knowledge, the best EC 50 of the natural product, mangiferin (a xanthone glucoside from the leaves of Mangifera indica and the root of Anemarrhena asphodeloides ), was more than 100 µM. 130 In addition to GK activation activity, mangiferin has various other functions via diverse targets, such as antioxidant, antimicrobial, antidiabetic, antiallergic and anticancer, 131 which exhibits its nonselective characteristic feature.…”
Section: Discussionmentioning
confidence: 80%
“…Test compounds that are high in order formed π-π bonds, hydrophobic bonds and H-bonds with GK and AR, while metformin and miglitol showed only H-bonding. Moreover all ligands interact with allosteric binding site of GK (Matschinsky et al, 2006 ; Min et al, 2017 ) and AR (Antony and Vijayan, 2015 ). The ligands order of affinity against AA was found as; DPAA > DPC1 > DMC1 > DOC1 > CPAA > PFA > miglitol.…”
Section: Discussionmentioning
confidence: 99%